POSSIBLE WAYS OF REORGANIZING PRIMARY HEALTH CARE IN GYNECOLOGY IN THE LIGHT OF EFFECTIVE EARLY DIAGNOSIS OF REPRODUCTIVE SYSTEM CANCER - L. A. Ashrafyan; I. B. Antonova; I. O. Basova; S. V. Ivashina; A. V. Lyustik; M. A. Antoshechkina (Опухоли женской репродуктивной системы)
The oncological care system, established in Russia as early as the mid-twentieth century, is presently unable to provide an effective early diagnosis of malignancies, including reproductive system tumors. The past 10-15 years have become the years of missed oppor- tunities and losses to a greater extent than modernization of a primary obstetric and gynecological care system. This paper deals with this problem and a search for its solution.